Paternal low protein diet and the supplementation of methyl-donors impact fetal growth and placental development in mice. (1st January 2021) - Morgan, Hannah L.; Aljumah, Arwa; Rouillon, Charlène; Watkins, Adam J.
Abstract: Introduction: Paternal low-protein diet can alter sperm methylation status, fetal growth and program offspring ill-health, however its impact on the placenta remains poorly defined. Here we examine the influence paternal low-protein diet has on fetal and placental development and the additional impact of supplementary methyl-donors on fetoplacental physiology. Methods: Male C57BL/6J mice were fed a control normal protein diet (NPD; 18% protein), a low-protein diet (LPD; 9% protein) or LPD with methyl-donor supplementation (MD-LPD; choline chloride, betaine, methionine, folic acid, vitamin B12) for a minimum of 8 weeks. Males were mated with 8–11 week old female C57BL/6J mice and fetal and placental tissue collected on embryonic day 17.5. Results: Paternal LPD was associated with increased fetal weights compared to NPD and MD-LPD with 22% fetuses being above the 90th centile for fetal weight. However, LPD and MD-LPD placental weights were reduced when compared to NPD. Placentas from LPD fathers demonstrated a reduced junctional zone area and reduced free-fatty acid content. MD-LPD placentas did not mirror these finding, demonstrating an increased chorion area, a reduction in junctional-specific glycogen staining and reduced placental Dnmt3b expression, none of which were apparent in either NPD or LPD placentas. Discussion: A sub-optimal paternal diet can influence fetal growth and placental development, and dietary methyl-donor supplementation alters placental morphology and gene expression differentially to that observed with LPD alone. Understanding how paternal diet and micro-nutrient supplementation influence placental development is crucial for determining connections between paternal well-being and future offspring health. Highlights: Paternal low protein diet (LPD) increased late gestation fetal weight. Supplementing the LPD with methyl donors (MD-LPD) normalised fetal weight. Placental weight and morphology are altered by both LPD and MD-LPD. Placental metabolite content and gene expression were perturbed by paternal LPD and MD-LPD.